School-parent relationship : the expectations of school administrators, teachers and parents of selected international schools in Kuala Lumpur - Mohamed, Abdullahi Abdi (International Islamic University Malaysia, 1998)
The purpose of the study was to investigate the expectations of school administrators, teachers and parents about the school-parent relationship in two international schools in Kuala Lumpur. The study focused on issues pertaining to school administrations, students' discipline, school-parent communication and homework supervision. Moreover, the research sets out to assess whether significant differences existed between the expectations of school administrators, teachers and the parents about the school-parent relationship. The study sample consisted of 165 respondents who were randomly selected from the school administrators, teachers and parents ofMont'kiara International School and Mutiara International Grammar School. The study utilized a single, selfconstructed questionnaire to collect the data. Descriptive and inferential statistics (chi-square) were used to analyze the data and an open-ended section was used to enrich information. The findings of the study showed that school administrators and teachers were expected to cooperate with parents in terms of listening to parents' complaints and getting parents' involved in the decision making of the school. Based on parents' expectation about decision making in school matters it appears that parents do not like to be decision-makers. School administrators and teachers supported the idea that the school should deal with disciplinary problems with individual parents. In contrast, the vast majority of parents felt that the PT A and school administrators should solve disciplinary problem together. School administrators and teachers preferred that parents communicate with the school individually. School administrators and teachers did not agree with the idea of organizing workshops for parents at the beginning of every semester on how to supervise their children's homework. The majority of the parents agreed that teachers should reveal a student's academic problems to his or her parents. Finally, there was no significant difference between the expectation of school administrators, teachers and the parents regarding the school-parent relationship except in the area ofresponsibility for students' discipline.